All-cause mortality effects of replacing sedentary time with physical activity and sleeping using an isotemporal substitution model: a prospective study of 201,129 mid-aged and older adults - Stamatakis, Emmanuel (Int J Behav Nutr Phys Act, 2015)
BACKGROUND: Sedentary behaviour, sleeping, and physical activity are thought to be independently associated with health outcomes but it is unclear whether these associations are due to the direct physiological effects of each behaviour or because, across a finite 24-hour day, engagement in one behavior requires displacement of another. The aim of this study was to examine the replacement effects of sedentary behaviour (total sitting, television/computer screen time combined), sleeping, standing, walking, and moderate-to-vigorous physical activity on all-cause mortality using isotemporal substitution modelling. METHODS: Longitudinal analysis (4.22 ± 0 · 9 years follow-up/849,369 person-years) of 201,129 participants of the 45 and Up study aged ≥45 years from New South Wales, Australia. RESULTS: Seven thousand four hundred and sixty deaths occurred over follow-up. There were beneficial associations for replacing total sitting time with standing (per-hour HR: 95 % CI: 0.95, 0.94–0.96), walking (0.86, 0.81–0.90), moderate-to-vigorous physical activity (0.88, 0.85–0.90), and sleeping in those sleeping ≤ 7 h/day (0.94, 0.90–0.98). Similar associations were noted for replacing screen time. Replacing one hour of walking or moderate-to-vigorous physical activity with any other activity class was associated with an increased mortality risk by 7–18 %. Excluding deaths in the first 24 months of the follow up and restricting analyses to those who were healthy at baseline did not materially change the above observations. CONCLUSION: Although replacing sedentary behaviour with walking and moderate-to-vigorous physical activity are associated with the lowest mortality risk, replacements with equal amounts of standing and sleeping (in low sleepers only) are also linked to substantial mortality risk reductions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12966-015-0280-7) contains supplementary material, which is available to authorized users.